علاقة عمل المرأة بالترابط الأُسري (Journal of the College of Education for Women, 2019)
The significance of this research lies in revealing the actual role of the range ofthe effect of women's participation in family life. Both the historic and theconclusive curriculum were used. The researcher was able to achieve severalresults; one of the important of them is the existence of the obstacles that workingwomen face in life, though they do not stop the woman and her work.